Die Familien-Fideikommissbibliothek des Hauses Habsburg-Lothringen 1835-1918: Metamorphosen einer Sammlung - Huber-Frischeis, Thomas; Valenta, Rainer; Knieling, Nina (2021)
The book deals with the history of the Fideikommissbibliothek (entailment library) of the House of Habsburg-Lorraine from the perspective of cultural history. The collection was subject to various transformations: Originally a princely private collection, it became a memory space of the ruling dynasty and scientific institution.